Spatial dimensions of cooperation aimed at innovation - Pieter Bruijn (European Regional Science Association (ERSA), 2003)
In the contemporary debate on innovation and economic development, innovation is associated with economic networks and co-operation between innovating firms. Moreover, innovation is associated with regional clustering of activities. Most research on clusters employ case study research. This research takes a different perspective by combining regional input-output data and results of the European Community Innovation Survey. On this empirical material, a model has been developed that aims to quantify regional dimensions of innovation. Conclusions focus on the character of clustering. Regional presence of innovators has a significant effect for the innovative output of innovators, innovating in partnership. Regional thickness in the production chain, as measured through intermediate deliveries and supplies, does not have a significant effect on the innovative output of innovators. For innovating firms which do not innovate in partnership we did not find statistically significant effects of clustering on innovative output. International partnerships seem, compared to local networking, more decisive for innovation. Furthermore, we found indication that partnership is complementary to the use of external information.
Keywords: 330